Occurrence of aflatoxins and fumonisins in maize grains harvested in the territory of Belgrade (R. Serbia) from 2018 to 2022 - Krnjaja Vesna; Stanković Slavica; Obradović Ana; Mandić Violeta; Petrović Tanja; Stanišić Nikola; Delić Nikola (Biotechnology in Animal Husbandry, 2023)
The aim of this study was to evaluate the occurrence of total aflatoxins (AFs) and type-B fumonisins (FBs) in 65 maize grain samples collected during harvest in 2018 (13 samples), 2019 (11 samples), 2020 (9 samples), 2021 (14 samples) and 2022 (18 samples) from different locations in suburb of Belgrade (Republic of Serbia). The average levels of AFs and FBs in mycotoxin-positive samples were 5.43 and 2910 µg kg-1 (2018), 5.28 and 2710 µg kg-1 (2019), 2.35 and 10980 µg kg-1 (2020), 6.81 and 4950 µg kg-1 (2021) and 5.32 and 20310 µg kg-1 (2022), respectively. In 23.08% (2018), 18.18% (2019), 22.22% (2020), 64.29% (2021) and 27.78% (2022) of maize samples, the co-occurrence of AFs and FBs was established. The maximum limits of 10 µg kg-1 for AFs in maize and 4000 µg kg-1 for FBs in unprocessed maize prescribed by regulations of Serbia and the European Union were exceeded for AFs in 14.29% (2021) and 5.56% (2022) of maize samples and for FBs in 7.69% (2018), 66.67% (2020), 28.57% (2021) and 41.67% (2022) of maize samples. Multiple linear regression analyses showed a statistically significant influence of climate factors (air temperature, relative humidity and total rainfall) in July-September (2018-2022) on FBs levels. These results indicate the need for continuous monitoring of the health status of harvested maize grains and risk assessment of the potential presence of mycotoxins in the food chain to avoid adverse effects on human and animal health.